Theoretical investigation of the Co-occurrence of superconductivity and antiferromagnetism in iron-based high-temperature superconductors - Sherka, Gebru Tesfaye; Shiferaw, Dagne Atnafu (Frontiers in Physics, 2024)
In this research work, the Co-occurrence of superconductivity and antiferromagnetism in Ca 0.74 (1) La 0.26 (1) (Fe 1-x Co x ) As 2 iron-based high-temperature superconductors have been investigated. Based on the multi-band nature of Ca 0.74 (1) La 0.26 (1) (Fe 1-x Co x ) As 2 iron-based superconductors, a two-band model Hamiltonian that contains intra-and inter-bands is developed.By employing the matrix form of the temperature-dependent Green's function formalism with the two-band Hamiltonian, the mathematical expressions of superconducting transition temperature as functions of the superconducting order parameter and antiferromagnetic translational temperature as a function of the magnetic order parameter are obtained, respectively. The plotted graph of the superconducting and magnetic temperature as a function of the magnetic order parameter indicates a clear possibility of Co-occurrence of superconductivity and the antiferromagnetic order parameter in Ca 0.74 (1) La 0.26 (1) (Fe 1-x Co x ) As 2 iron-based superconductors in the range of magnetic order parameters between 2.3 meV and 6.07 meV, which is in good agreement with experimental observations. This research contributes to understanding the complex behavior of high-temperature superconductors and provides valuable technological applications for other fields.